LITERATURE REVIEW THE EFFECT OF GIVING EXTRACTS OF BASIL (Ocimum basilicum L.) TO THE SGOT AND SGPT LEVELS IN WHITE RAT (Rattus norvegicus) STRAIN MALE WISTAR WITH HIGH FAT FED - Fitriani, Dita; Hasbie, Neno Fitriyani; Prasetya, Toni; Rusdiansyah, Ferza (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Background: Fatty liver (fatty liver) or Non-lcoholic Fatty Liver Disease (NAFLD) is an excessive accumulation of fat (lipids) in liver cells. Fatty liver is generally associated with metabolic syndrome, obesity, diabetes, and hyperlipidemia. Insulin resistance causes an increase in the entry of Free Fatty Acids (FFA) into the liver and occurs due to the failure of insulin to suppress hormone-sensitive lipases. Basil contains chemical compounds such as phenolic compounds and flavonoids that act as antioxidants that can ward off free radicals. Experimental animals use mice because they have physiological similarities to humans and are easy to keep experimental animals. Purpose: This study aims to determine the effect of basil extract (Ocimum basilicum L.), the effective dose and the duration of the effective dose in reducing SGOT and SGPT levels. Methods Research: The research design used was a descriptive research design. Literature review using the PubMed database and ncbi.mlm.nih.gov using keywords used in data searches to search for journals related to basil extract, SGOT, SGPT, rats, and high-fat diets. Results: The results of the research from 8 journals that have been reviewed found that the levels of SGOT and SGPT had decreased significantly. Basil extract (Ocimum basilicum L.) has been proven preclinically and clinically to reduce AST and ALT levels. Conclusion: The conclusion that can be drawn is that the extract of basil (Ocimum basilicum L.) can reduce levels of SGOT and SGPT. Keywords: Basil Extract, High Fat Diet, NAFLD, SGOT, SGPT, White Rat